Socioeconomic Status, Biological Aging, and Memory in a Diverse National Sample of Older US Men and Women. (8th November 2022) - Avila-Rieger, Justina; Turney, Indira C.; Vonk, Jet M.J.; Esie, Precious; Seblova, Dominika; Weir, Vanessa R.; Belsky, Daniel W.; Manly, Jennifer J.
Abstract : Background and Objectives: Exposure to socioeconomic disadvantage is associated with early-onset cognitive aging. Biological aging, the progressive loss of system integrity that occurs as we age, is proposed as a modifiable process mediating this health inequality. We examined whether socioeconomic disparities in cognitive aging in mid-to late-life adults is explained by accelerated biological aging similarly across race, ethnicity, and sex/gender. Methods: Data were from a prospective cohort study of the US Health and Retirement Study DNA methylation substudy. Socioeconomic status (SES) was measured from years of education and household wealth at baseline. The extent and pace of biological aging were quantified using 3 DNA methylation measures: PhenoAge, GrimAge, and DunedinPoAm. Cognitive aging was measured from repeated longitudinal assessments of immediate and delayed word recall. Latent growth curve modeling estimated participants' level of memory performance and rate of decline over 2–11 follow-up assessments spanning 2–20 years. Multiple-group models were estimated to assess whether the relationship between SES and memory trajectories was mediated by biological aging across racial-ethnic by sex/gender subgroups. Results: Data from a total of 3, 997 adults aged 50–100 years were analyzed. Participants with lower SES had a lower memory performance, had a faster decline, and exhibited accelerated biological aging (SES effect size associations [β] ranged from 0.08 to 0.41). Accelerated biological aging was associated with decreased memory performance and faster memory decline (effect size range 0.03–0.23). SES-biological aging associations were the strongest for White men and women and weakest for Latinx women. The relationship between biological aging measures and memory was weaker for Black participants compared with that for White and Latinx people. In mediation analysis, biological aging accounted for 4%–27% of the SES-memory gradient in White participants. There was little evidence of mediation in Black or Latinx participants. Discussion: Among a national sample of mid-to late-life adults, DNA methylation measures of biological aging were variably associated with memory trajectories and SES across White, Black, and Latinx mid-to late-life adults. These results challenge the assumption that DNA methylation biomarkers of aging that were developed in primarily White people can equivalently quantify aging processes affecting cognition in Black and Latinx mid-to late-life adults.